Factors affecting ability to achieve asthma control in adult patients with moderate to severe persistent asthma. (2nd July 2016) - Scott, Lyne; Li, Marilyn; Thobani, Salima; Nichols, Breck; Morphew, Tricia; Kwong, Kenny Yat-Choi
Abstract: Objective : Despite the use of optimal therapy and guidelines, the rate of asthma control is suboptimal in adult populations. Purpose of this study is to describe factors associated with ability to achieve well-controlled asthma over time for adult patients treated in a tertiary medical center-based asthma outpatient specialty clinic. Methods : Existing clinical data collected for 320 adult patients enrolled in a hospital-based outpatient asthma specialty clinic from July 1, 2003 through June 30, 2011 evaluated time to achieve well-controlled asthma and factors associated with well-controlled asthma such as adherence and lack of previous exacerbations. Results : Adherence to prescribed therapy ( p = 0.004) and no previous asthma related ED visits ( p = 0.004) were associated with well-controlled asthma for moderate persistent baseline. BMI on a continuous spectrum ( p = 0.120) and the diagnosis of allergic rhinitis ( p = 0.769) were not independently significant. Body-mass-index (BMI) in combination with adherence did influence ability to achieve well-controlled asthma ( p < 0.05). Adherence ( p = 0.615), allergic rhinitis ( p = 0.172), BMI continuous scale ( p = 0.074) and visit interval <90 days ( p = 0.653) were not independently associated with likelihood of achieving well-controlled asthma in severe persistent asthmatics. Significance of particular factors in combination (adherence, allergic rhinitis, sex, BMI) showed dependency on other variables in achieving well-controlled asthma. Conclusions : Different factors are associated with asthma control for different patient subpopulations. Adherence to standard therapy did not improve obese (BMI > 30) patients' ability to achieve asthma control. Female patients were less likely to obtain well-controlled asthma per unit increase of BMI. Multiple factors must be addressed to optimize attaining asthma control.